2022
DOI: 10.1038/s41598-022-12292-4
|View full text |Cite
|
Sign up to set email alerts
|

Complex spatial light modulation capability of a dual layer in-plane switching liquid crystal panel

Abstract: Complex spatial light modulator (SLM), which can simultaneously control the amplitude and phase of light waves, is a key technology for wide-range of wave-optic technologies including holographic three-dimensional displays. This paper presents a flat panel complex spatial light modulator that consists of dual in-plane switching liquid crystal panels with double-degrees of freedom of voltage inputs. The proposed architecture features single-pixel level complex light modulation enabling complex light modulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Such redundancies can be reduced to shrink down the size and computation load of the model. Additionally, the system can take advantage of advanced features of SLM such as high framerate or complex modulation capability 57 . Several studies have recently reported that utilization of temporal multiplexing helps speckle reduction and image quality enhancement 48,58 .…”
Section: Discussionmentioning
confidence: 99%
“…Such redundancies can be reduced to shrink down the size and computation load of the model. Additionally, the system can take advantage of advanced features of SLM such as high framerate or complex modulation capability 57 . Several studies have recently reported that utilization of temporal multiplexing helps speckle reduction and image quality enhancement 48,58 .…”
Section: Discussionmentioning
confidence: 99%
“…A simple Jones matrix method is employed to describe the characteristics of the transmitted light. 13,16,17) The transmission characteristics of a single pixel of the dual-layer IPS SLM are described by…”
Section: Theoretical Analysismentioning
confidence: 99%
“…For the amplitude CGH ( ) A x y , experiment, the value of ( ) A x y , is input into a single IPS SLM. 13) Figure 4 presents the numerical simulation and experimental results of the designed far-field CGH.…”
Section: Validation Of Full Color Complex Modulationmentioning
confidence: 99%
See 1 more Smart Citation